006.4 Azithromycin versus doxycycline for urogenital chlamydia: a randomised clinical trial in females and males in youth correctional facilities. (13th September 2015) - Geisler, WM; Uniyal, A; Lee, JY; Lensing, SY; Johnson, S; Perry, RCW; Kadrnka, CM; Kerndt, PR
Abstract : Background: Urogenital Chlamydia trachomatis infection ("chlamydia") remains highly prevalent and causes significant reproductive morbidity. Earlier randomised chlamydia treatment trials comparing azithromycin 1g versus a 7-day regimen of doxycycline 100mg twice daily reported high cure rates, but used less sensitive diagnostics and results may have been confounded by chlamydia re-exposure or doxycycline nonadherence. Recent studies have raised concern about azithromycin efficacy for chlamydia. Methods: We conducted a randomised trial comparing azithromycin versus doxycycline for chlamydia in males and females in youth correctional facilities (YCFs) to evaluate for noninferiority of azithromycin compared to doxycycline. Treatment was directly observed and participants had no furloughs from the YCF throughout the study. The primary endpoint was treatment failure at 28 days after treatment initiation, determined by nucleic acid amplification test results, sexual history, and C. trachomatis OmpA genotyping. Results: Of 567 participants enrolled, 284 were randomised to azithromycin and 283 to doxycycline. There were 155 participants in each treatment arm comprising the per protocol population: 65% male and 35% female. No treatment failures occurred in the doxycycline arm. In the azithromycin arm, five treatment failures occurred (3.2%; 95% CI: 0.4–7.4%): four were males (3.9%; 95% CI: 1.1–9.7%) and one female (1.9%; 95% CI: 0.0–10.1%). The observed failure rate difference in the treatments was 3.2%, with a 90% upper CI of 5.9%, exceeding the predetermined 5% cutoff for establishing azithromycin noninferiority. Conclusion: Doxycycline had a 100% cure rate for chlamydia. Noninferiority of azithromycin to doxycycline was not established in this study, although azithromycin treatment failures occurred infrequently and the high azithromycin cure rate was consistent with earlier chlamydia treatment trials. Because of possible chlamydia treatment failures when azithromycin is used, further surveillance is needed and doxycycline might be considered for persons with suspected chlamydia treatment failure following azithromycin treatment. Disclosure of interest statement: Nothing to Declare.